The failure mechanisms of fasteners under multi-axial loading. (November 2019) - Cao, Zhenzhong; Brake, M.R.W.; Zhang, Dingguo
Abstract: Fasteners in assemblies are often subjected to multi-axial loading; however, the role of load angle and the assembly design/geometry on the failure of fasteners are not well understood. Existing experimental data often convolutes multiple sources of uncertainty. Thus, numerical modeling is needed to make accurate conclusions about the failure mechanisms of fasteners. This paper investigates the mechanics that controls the loading angle effects on the mechanical response of fasteners by using a simple finite element bolt model without threads. The material model of this model is calibrated against tensile testing data, which minimizes the contribution of the fixture to the bolt's response. The calibrated material model is then used to investigate the loading fixture effects (including the fixture gap, compliance, and double shear loading configuration) on the mechanical response of the fasteners. After identifying the fixture parameters that the fastener's response is most sensitive to, a model of a simplified fixture is validated against experimental results. This investigation reveals that the loading angle effects and most of the loading fixture effects on fasteners' mechanical response are attributed to the change of stress concentrations at the contact tips. The primary contributions of this paper are novel insights into the failure mechanisms of fasteners, and that a reduced model of a fastener can be used to predict its constitutive behavior accurately. Highlights: A simplified fastener-test fixture model is developed to investigate failure mechanisms under mixed shear and tensile loading The model is validated against multiple sources of experimental data from the literature The model is used to investigate the fixture's effects on the measured constitutive properties of a fastener This work highlights the need to account for the test fixture design in extracting properties from fastener testing